Prospect and challenges of electric vehicle adaptability: an energy review Malaysia - Rahman, Mohammed Ataur; Mohammed, Azri; Kyaw, Myo Aung; Ismail, Ahmad Faris; Mohiuddin, A. K. M.; Ihsan, Sany Izan (Sila Science, 2018)
The development of commercialized electric vehicles (EVs) has yet to be accelerated due to the lack of electrification. Electric vehicles charged with low-emission electricity are one of the key options to reduce emissions in passenger road transport. The introduction of electric vehicles will inevitably lead to a greater interaction between the mobility and the electricity generation. The electric car penetration reaches higher levels; the electricity demand from electric cars will become a relevant factor in the energy system and impacts the operation of power plants and grid infrastructure. Different smart charging strategies could be considered on the chosen goal of electric vehicle demand management: reducing grid constraints, maximizing utilization of renewable energy production to reduce CO2 emissions or minimizing emission by shifting electricity generation from coal and gasoline power plant to hydropower plant. This paper presents the eco-friendly smart electric vehicle body panel which considered as an energy generator from the solar power and vehicle deceleration and storage them unit discharged to meet the auxiliary power system demand. It would be able to reduce the grid constraints and incremental power plant capacity. The smart body panel is expecting to generate the renewable energy about 3.66 kW from solar power and vehicle deceleration from 125 km/h to 25 km/h and also the save vehicle propelling power about 10% by cutting away the vehicle weight about 15%